Cocteau au cirque: The Poetics of Parade and "Le Numéro Barbette" - Jennifer Forrest (Studies in 20th & 21st Century Literature, 2003)
Parade (1917) was a joint effort production with libretto by Jean Cocteau music by Erik Satie, decor, costumes, and curtain by Pablo Picasso, and choreography by Léonide Massine. It was not only Cocteau's first truly original work, but, as Pierre Gobin contends, Parade is central to an understanding of the structures that would inform all of his subsequent work. Equally central, proposes Lydia Crowson, is Cocteau's July 1926 Nouvelle Revue Française article on "Le Numéro Barbette." The essay on the transvestite striptease trapezist Barbette offers a poetics of the theater that will have changed little by the time of his last play, L'Impromptu du Palais Royal. The underlying system structuring the Coctelian poetics perceived by Gobin and Crowson is perhaps neither in Parade nor in "Le Numéro Barbette" alone, but in both as they propose a poetics of Coctelian art as illusion, and reference and actualize the semantic register of a particular signifying system: not the fairground parade, as contends Gobin and other critics, but the circus and circus culture. But while Parade and "Le Numéro Barbette" share a circus-related theme, the circus does not function merely as a metaphor. Each work in a different way appropriates and promotes rather the circus's revolutionary orientation toward space, its creation of "real" time, and its undermining of social signifying systems, in particular those pertaining to race and gender. The circus space is like that of dreams in that it permits the irresolution and co-existence of the sort of contradictions cited by Guillaume Apollinaire in the celebrated program notes for Parade, and produced by Barbette in his aerial number. This he learned from the circus. Parade and "Le Numéro Barbette" are indeed pivotal texts in the formulation of Cocteau's very twentieth-century poétique.
Keywords: Parade; Jean Cocteau Erik Satie; music; decor; costumes; and curtain; Pablo Picasso; Léonide Massine; Pierre Gobin; Lydia Crowson; Nouvelle Revue Française; Le Numéro Barbette; Barbette; poetics of the theater; L& #x27; Impromptu du Palais Royal; Coctelian poetics; Coctelian art; illusion; circus; circus culture; space; time; race; gender; circus space; irresolution; Guillaume Apollinaire; twentieth-century; poétique